2016
DOI: 10.1210/jc.2015-4125
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Hypoxia, Inflammation, and Fibrosis in Obese Insulin-Sensitive and Obese Insulin-Resistant Subjects

Abstract: We confirmed that adipose tissue inflammation and fibrosis play an important role in the pathogenesis of insulin resistance independent of obesity in humans. Whether hypoxia is simply a consequence of adipose tissue expansion or is related to the pathogenesis of obesity-induced insulin resistance is yet to be understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(137 citation statements)
references
References 31 publications
12
122
1
2
Order By: Relevance
“…Although Mmp7 has known roles in tissue fibrosis (48), wound healing, and cell migration (47), its exact function in AT remains to be elucidated. A recent report describes a significant induction of Mmp7 expression in subcutaneous AT from obese, insulin-resistant humans when compared with obese, insulin-sensitive humans (49). Future studies will focus on the relationship of Mmp7 to adipocyte OSM signaling and AT inflammation in obesity.…”
Section: Discussionmentioning
confidence: 97%
“…Although Mmp7 has known roles in tissue fibrosis (48), wound healing, and cell migration (47), its exact function in AT remains to be elucidated. A recent report describes a significant induction of Mmp7 expression in subcutaneous AT from obese, insulin-resistant humans when compared with obese, insulin-sensitive humans (49). Future studies will focus on the relationship of Mmp7 to adipocyte OSM signaling and AT inflammation in obesity.…”
Section: Discussionmentioning
confidence: 97%
“…Obesity constitutes a chronic low-grade inflammatory condition, leading to robust morphological and functional changes within adipose tissue (AT), including the accumulation of immune cells, the dynamic remodeling of the extracellular matrix (ECM), and the altered production of adipokines, among others 1,2 . An increased macrophage recruitment into AT and their polarization towards a proinflammatory M1 phenotype represents a hallmark of obesity-associated inflammation [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…We and others have reported decreased adipose tissue pO 2 in obese as compared to lean participants 24 28. However, Goossens et al 29 reported reduced oxygen extraction by adipose tissue resulting in increased adipose tissue pO 2 in obese versus lean participants.…”
Section: Evidence Of Adipose Tissue Hypoxia In Obese Humanmentioning
confidence: 51%
“…Perhaps inconsistent results were due to small sample size of these studies or differences in methods used to measure oxygen tension. Goossens et al 29 measured pO 2 continuously in the perfusate of a microdialysis probe whereas others24 28 used a small Clarke electrode placed directly in touch with adiposytes. The decreased oxygen extraction by adipose tissue of obesity reported by Goossens et al 29 is in contrast with a recent study in mice which showed HFD-induced obesity resulted in uncoupling of adipocyte respiration leading to increased oxygen consumption and relative adipocyte hypoxia 30…”
Section: Evidence Of Adipose Tissue Hypoxia In Obese Humanmentioning
confidence: 99%